Potential Therapeutic Roles of Icariin in Inflammatory Diseases: From Molecular Mechanisms to Clinical Translation Prospects - Sirui Du; Weifeng Li; Meixiu Jiang (Antioxidants, 2026)
Inflammatory diseases are caused by overactivation of the immune system and lead to tissue damage; their high incidence and complications seriously threaten human health. Currently, non-steroidal anti-inflammatory drugs (NSAIDs) and immunosuppressants are the mainstay of clinical practice, but their long-term use can cause gastrointestinal damage, drug resistance, and other problems. In recent years, traditional Chinese medicine has become a research hotspot for the treatment of inflammatory diseases, among which Icariin (ICA), the main active ingredient of Epimedium, has demonstrated significant anti-inflammatory potential. In this review, a comprehensive literature search of PubMed and Web of Science was conducted, and original studies on the anti-inflammatory effects and mechanisms of ICA were included. The roles and mechanisms of ICA in inflammatory diseases in different systems are summarized. Specifically, ICA suppresses NF-κB and MAPK signaling, inhibits NLRP3 inflammasome activation, and activates the Nrf2/HO-1 antioxidant axis, thereby reducing the production of pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β. Overall, the current evidence indicates broad anti-inflammatory effects of ICA across multiple organ systems, particularly in atherosclerosis and myocardial infarction; however, clinical translation is limited by poor bioavailability and the lack of standardized dosage data. Future efforts should focus on pharmacokinetic optimization and well-designed clinical trials to facilitate its application in inflammatory diseases.